Abstract ID:364 MR-Image guidance – Clinical perspective. (December 2018) - Lohr, Frank
Abstract : Purpose: The ideal situation for radiotherapy would be a treatment under more or less static conditions in an ideal dosimetric situation with permanent control of the position of tumor, organs-at-risk (OAR) and patient surface. Methods: This presentation will outline the current state of the art and explore, if/how/where in-room MR-guidance may go beyond current strategies and what requirements must be fulfilled on the way as layed out in a previous publication [1]. Results: If there is a necessity for on line MR-guidance, there is a general necessity for broad use of advanced image guidance strategies, particularly as successful screening programs such as those for lung cancer and potentially even pancreatic cancer are established, as this potentially leads to more localized disease being treated. Several such strategies are now available but are underutilized, typically for lack of funding or perceived complexity. Online MR-image guidance has the ability to simultaneously image and target the cancer and is more intuitive when integrated into a single system and the high image quality of MRI-guidance may further facilitate the education of personnel and facilitate adaptive RT approaches. In addition, online MR-guidance systems may in the future better respond changing cancer physiology over the treatment, facilitate differential targeting of tumor, lymphatic tissue etc. and offer other added values not yet broadly established (e.g. targeting of atrial fibrillation) or completely identified. Conclusions: There is no doubt that the use of advanced imaging on a broad scale is needed. It is a significant clinical problem that a large number of RT devices are still in clinical use without the capability for 3D-imaging and beam gating. As a next step, online MR-image guidance may offer a significant number of benefits over established approaches that may open new roads in radiotherapy.